PSAK 45: Recording Solutions for Non-Profit Accounting in PT INKA Labor Union - M. Agus Sudrajat; Nik Amah; Maya Novitasari; Moh. Ubaidillah; Mawar Puspitasari; Mahesti Cahayuni (Jurnal Akuntansi dan Pajak, 2022)
This study aims to determine the financial statements of PT INKA (Persero) union organization, to analyze the suitability of the presentation of financial statements at PT INKA (Persero) Labor Union organization, then to reconstruct the financial statements of PT INKA (Persero) Labor Union organization in accordance with PSAK 45. A non-profit organization is an organization whose main goal is to support an issue or situation in attracting the public for a non-commercial purpose. PSAK 45 statement intends to regulate the financial reporting of non-profit entities. By having the reporting rules, it is hoped that the financial statements of non-profit entities can be more easily understood, have relevance, and have high comparability. The Workers Union of PT Industri Kereta Api (Persero) is an organization which is a forum/institution for employees of PT Industri Kereta Api (Persero). The method used in this research was qualitative research with descriptive method. The results of the research that have been carried out show that the PT INKA Labor Union has recorded cash disbursements and income properly, as evidenced by the existence of financial reports that are in accordance with the organization's AD/ART. However, the financial statements of PT INKA (Persero) Labor Union are not in accordance with PSAK 45 and a reconstruction will be carried out so that the resulting financial reports can be more easily understood, have relevance, and have high comparability.